Oral premalignant lesions: a clinicopathological study - Jagtap, Sunil Vitthalrao; Warhate, Pranita; Saini, Neerav; S. Jagtap, Swati; Chougule, P. G. (International Surgery Journal, 2017)
Background: A significant number of oral cancer cases present initially with precursor lesions. If detected earlier in disease course it will reduce the morbidity and mortality. The objective of this study was to evaluate the clinical presentation and various histopathological types of premalignant lesions. Methods: This is descriptive, observational, analytical type of study of five-year duration. The detail clinical presentation, relevant investigation and histopathological study on biopsy tissue stain with H and E was done and the data is analysed. Results: During study period, 173 cases having oral lesions were observed. Among these 38 cases showed oral premalignant lesions. The most common age group affected was in between 50 to 59 years. The male predominance was noted. Male to female ratio was 1.9:1. The location of the lesions were buccal mucosa (55.26%), tongue (26.31%), gingiva (7.90%), alveolus (5.26%), lip (2.6%), retromolar area (2.63%) was noted. The common etiological factor observed was tobacco chewing. On histopathological features, cases were of leukoplakia 68.41%, oral lichen planus 13.16%, oral submucous fibrosis 7.90%, actinic cheilitis-7.9%, and oral erythroplakia 2.6%. Conclusions: In this study, various oral premalignant lesions were observed. Their clinical and histopathological evaluation was done. Oral leukoplakia was most common lesion in the present study. Buccal mucosa was the most common site. Tobacco chewing habit was the common risk factor observed. Early detection of premalignant oral lesion is of utmost importance to prevent further morbidity as these lesions further progress to oral cancer.